Penerapan Model Problem Based Learning Untuk Meningkatkan Berpikir Kritis Siswa Kelas II Pada Mata Pelajaran Pendidikan Pancasila di SD Negeri Srondol Wetan 05 - Nova Dwiyanti; Alifia Fatimah Azzahra; Nur Indah Wahyuni; Fitriani Sulistiyorini (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study was conducted to determine whether there is an increase in students' critical thinking by using a problem-based learning model at school. In line with the new paradigm of 21st century learning, which requires teachers to be able to present learning that can encourage students' activeness in the classroom during the learning process. The quality of students' critical thinking depends on the quality of their education, so teachers need to apply learning models that support the improvement of students' critical thinking in Pancasila Education subjects. The method used in writing this article is a qualitative research method. The results of this study can be concluded that there is an increase in students' critical thinking in Pancasila education learning subjects by using a problem-based learning model (Problem Based Learning), namely from cycle I Learners who get scores above KKM reach 70% of all students and in cycle II Learners who get scores above KKM reach 73% of all students. The level of completion of students in working on problems in cycle I is 92% and the level of completion of students in working on problems in cycle II is 93%.